Firewall para redes LoRaWAN - Figueira, Henrique Ricardo (2021)
This work addresses security issues in IoT protocols to prevent and mitigate cyberattacks on radio frequency networks that allow long-distance communication with low energy consumption, known as LoRa networks. The main objective was the development and evaluation of a firewall that blocks LoRa packets; it was also analyzed whether the proposed solution would harm the normal functioning of the gateway. To develop the firewall was necessary to analyze how the RisingHF-gateway software carried out the forwarding of packets and make changes to the code. After the development of the firewall, it was possible to verify that it is feasible to block LoRa packets through the device address and that the implemented solution does not interfere with the normal functioning of the code. The result of the research was the development of a firewall with rules that allow blocking or authorizing the retransmission of packets from one device.